Mathematical Simulation and Thermal State Analysis of Combustion Chambers for Power Systems - Kretinin, Alexander V.; Kirpichev, M.I.; Podvalny, Semen; Lutovac, Mitar; Podvalny, E.S. (International Journal of Industrial Engineering and Management, 2018)
Some problems of thermodynamic, hydraulic and thermal calculations of the thermal state analysis and performance of the liquid-propellant rocket engine design using neural network modeling are detected. The algorithm of the numerical decision of the hydrodynamics equations with representation of the decision on method of weighted residuals on the base of general neuronet’s approximation in the whole flow area is developed. There are presented some applications of neural-network algorithms usedin thermal calculations of the LRE chamber such as the simulation of hydraulic non-uniformity of fuel distributionamong the sprayers of LRE mixing devices. Article history: Received (18.10.2017); Revised (24.01.2018); Accepted (08.03.2018)